Temperature dependent fracture toughness of KNN-based lead-free piezoelectric ceramics. (1st August 2019) - Li, Yingwei; Liu, Yixuan; Öchsner, Paul-Erich; Isaia, Daniel; Zhang, Yichi; Wang, Ke; Webber, Kyle G.; Li, Jing-Feng; Rödel, Jürgen
Abstract: The fracture toughness of unpoled and electrically poled lead-free KNN-based piezoelectric ceramics with the composition of 0.92KNN-0.02Bi0.5 Li0.5 TiO3 -0.06BaZrO3 was investigated. Results reveal that at room temperature, the intrinsic fracture toughness (KI0 ) of the unpoled samples, evaluated by the near-tip crack opening displacement (COD) technique, is the lowest with a value of 0.70 MPa ⋅ m 0.5 ; the long (through-thickness) crack fracture toughness (KIvnb ), obtained by the single edge V-notch beam (SEVNB) technique, is the highest, with a value of 0.95 MPa ⋅ m 0.5 ; intermediate short surface crack fracture toughness (KIsc ) of 0.86 MPa ⋅ m 0.5 was determined by the surface crack in flexure (SCF) technique. These results were rationalized by the toughening behavior of the material combined with the crack geometry-dependent stress intensity evolution during crack propagation. With increasing temperature, KIvnb and KIsc decrease, and become nearly identical at 350 °C, suggesting an absence of toughening. For electrically poled samples, their room temperature fracture toughness was characterized by both SCF and SEVNB techniques, with values of 0.88 MPa ⋅ m 0.5 and 0.99 MPa ⋅ m 0.5, respectively, slightly larger than the values measured for unpoled samples. Nonlinear electric field-strain and stress-strain analysis of the material was also employed during electric field loading, mechanical compression and four-point bending in order to quantify crack tip shielding by domain switching and the actual stress at the point of instable crack propagation. Graphical abstract: (a) Comparison between the intrinsic fracture toughness and fracture toughness of KNN-BLT-6BZ measured by SCF and SEVNB technique. For comparison, the calculated fracture toughness and the KIsc obtained with the nonlinear stress-strain behavior considered were also plotted. (b) Crack growth resistance KIR curves with toughening effect and the evolution of the stress intensity factor as a function of crack length. The red tangent dots represent the point at which unstable crack growth begins. The part of the KIR curve with red color denotes the stage in which stable crack growth will happen with increasing applied load. Image 1